Towards the development of an attitude scale to measure teacher morale - Aton, Pedrito A. (Animo Repository, 1996)
3rd work. -- The project study develops an Attitude Scale to Measure Teacher Morale for teachers whether they are from the public or private schools. It is a Likert type scale developed with the end view of: a) obtaining a baseline information for instructional as well as administrative planning and development b) diagnosing the strengths and weaknesses of the teachers c) determining the level of satisfaction of teachers and d) assessing the needs of the teachers. The scale development began with the identification of the objectives of the scale. Then the Table of Specifications was prepared. This table served as a guide for collating responses and item construction. The items constructed were based on the responses of the sample regarding the questionnaires given to them. The items were reviewed, rechecked, revised and changed depending upon the criteria intended for item writing before they were finally written in a pre-test form. The responses were checked, encoded in the computer and analyzed through Factor Analysis. With the use of this statistical procedure, items were able to cluster according to their communality and decisions were made on what specific factor is designated to the clustered items. The pool of items clustered in the specified factors served as the items for the final form. The final form contains 5 factors and 44 items. The study concluded that the Attitude Scale to Measure Teacher developed was intended to measure the psychological state of the teachers with regards to their performance and job satisfaction, rewards and recognition, relationship and attitude towards peers, efficiency and commitment and dedication.